Increasing Science Literacy Using a Guided Inquiry Learning Model Assisted by Interactive Modules on Elasticity Materials - Hasanah, Halimah Al; Nursabrina, Fakhira; Astra, I Made (Universitas PGRI Semarang, 2024)
This research aims to increase literacy using a guided inquiry learning model assisted by interactive modules on elasticity material. The study was carried out over three lessons with each lesson carried out in one complete cycle consisting of observation, reflection, design, and treatment. Data collection was carried out using an evaluation instrument in the form of a test using a questionnaire at the end of each cycle before the next cycle was carried out. The test instrument used contains indicators of science content aspects, science context aspects, and science process aspects. The results of the research showed that cycle III had the highest increase in each scientific literacy indicator with the science content indicator being 69.7%, the science context indicator being 68.7% and the science process indicator being 74.3%. So it can be concluded that increasing scientific literacy using the guided inquiry learning model assisted by interactive modules on elasticity material results in improvements in the good category.